Acute inflammatory demyelinating polyradiculoneuropathy in a newborn infant. (September 2016) - Anastasopoulou, Stavroula; Lindefeldt, Marie; Bartocci, Marco; Wickström, Ronny
Abstract: Background: Acute inflammatory demyelinating polyneuropathy (AIDP), also known as Guillain-Barré syndrome, is an immune-mediated polyneuropathy usually triggered by infections or vaccinations. In childhood AIDP is commonly described after the first year of life. Here, we present a case of a newborn infant with AIDP manifestation directly after delivery. Case study: A newborn girl with a healthy mother, without known exposure to immunomodulating factors, was admitted to the neuropediatric department due to ascending hypotonia, weakness, pain and areflexia in the lower extremities. The clinical presentation, laboratory and neurophysiological studies supported the diagnosis of AIDP. The infant showed first signs of clinical improvement following administration of intravenous immunoglobulin and her recovery was complete at one year. Conclusion: AIDP should be considered as a differential diagnosis in ascending hypotonia also in the neonatal period. Highlights: A newborn girl presented with ascending hypotonia, weakness and areflexia. The workup pointed to Acute inflammatory demyelinating polyneuropathy (AIDP). Administration of intravenous immunoglobulin was followed by prompt improvement. The recovery was complete at one year. AIDP as differential diagnosis should be considered also in early neonatal period.